Witch-Hunting in Assam: Myth or Reality - Lekha Borah; Madhushree Das (Space and Culture, India, 2019)
Assam, like many other parts across the country, often witnesses deaths, injuries, and miseries resulting from witch hunting, an atrocious practice and a socially sanctioned violence. Reiterated incidents of killings in the name of witch-hunting have alarmingly challenged the laws and have led to various anti-witch hunting programs. Often veiled under superstition, the factors that render this social menace unabated is a matter of grave concern for every conscious mind. Official records suggest 196 cases of the terrible violence to occur in the state between 1989-2014, but newspaper reports and other agencies present the actual social reality which echoes manifold of official records. The practice of witch-hunting, however, is not evenly distributed in all the areas of Assam, but have gripping roots in the customary beliefs of many tribal communities residing in the state. This research, therefore, is an attempt to illuminate the genesis of the witch hunt in Assam from the perspective of a crime having cross-community dimensions. Further, gaining insights from primary field survey and secondary data, it is evident that accessibility plays a trump card in this case of witchcraft in Assam along with the superstitious belief of the communities, intermingling with personal motives, illness and devious role of ojhas (village medicine men) which exaggerates the menace.